Pengaruh Endorsment dan Pembuatan Konten Viral Tiktok Pada Buying Behavior Customer - Rolando, Benediktus; Ferdian, Kevin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Tiktok is an application where their main focus is to provide short videos based on the user's interest and current trends that are happening. By taking advantage of said feature, a brand could increase the Tiktok user's brand awareness about their brand and products by making certain short videos using Endorsements and Viral Marketing concepts. This research aims to determine how Endorsements and Viral Marketing effects the Buying Behavior of a customer or a Tiktok user. This research is done by using the quantitative method with primary data coming from distributing questionnaires to one hundred (100) people who have the Tiktok application and have an understanding about the concept of Endorsements and Viral Marketing. Said primary data was analyzed using SPSS program through various tests that include validation (r > 0.3), reliability (Cronbach's Alpha > 0.6: Endorsement = 0.907, Viral Marketing = 0.889, Buying Behavior = 0.902), normality (skewness between -2 to +2 and kurtosis between -7 to +7), heteroscedasticity, and multicollinearity (VIF = 2.033 < 10). The multiple linear regression analysis showed significant positive effects of both Endorsement (β = 0.506, p < 0.001) and Viral Marketing (β = 0.562, p < 0.001) on Customer Buying Behavior. The F-test results (F = 158.809, p < 0.001) confirmed that both variables simultaneously influence buying behavior. From these statistical tests, this research concluded that Endorsements and Viral Marketing have a significant positive impact on customer buying behavior among Tiktok users.